Characterization and analysis of genetic diversity among different species of rose (Rosa species) using morphological and molecular markers - RAI, HENUKA; RAJU, D V S; M B, ARUN KUMAR; JANAKIRAM, T; NAMITA, NAMITA; KRISHNAN, S GOPALA; RANA, J C (The Indian Journal of Agricultural Sciences, 2015)
The present studies were undertaken to find out genetic diversity among twenty three genotypes of rose (Rosa species) using morphological and Random Amplified Polymorphic DNA (RAPD) markers. Morphological characterization was done for 16 different morphological traits and genetic diversity of rose species based on morphological characters was determined using Jaccard’s pair wise similarity coefficient. R.damascena var. Rani Sahiba and R. moschata showed highest diversity. Molecular characterization was carried out using 50 random amplified polymorphic DNA (RAPD) primers, out of which 26 produced 168 polymorphic fragments. Analysis of genetic similarity based on Jaccard’s pair wise similarity coefficient showed that R. moschata and R. tomentosa has the highest similarity. There was good concurrence between morphological and molecular characterization with considerable diversity in R. damascena. R. damascena var. Rani Sahiba and R. damascena var. Himroz have shown divergence from R. damascena var. Jwala. The members of the Section Indicae; R. indica var. odorata, R. indica major, R. chinensis viridiflora and R. bourboniana were also grouped together by molecular characterization. Kakinada rose, a local variety of South India was found to cluster with R. damascena var. Himroz through both morphological and molecular characterization. Both morphological and molecular analysis showed a high degree of variation in the rose germplasm which is an invaluable source of genetic diversity for rose improvement.